A study on the efficiency of Facebook and Twitter as used by the GMA Kapuso Foundation, Inc., ABS-CBN Foundation, Inc., and TV5 Alagang Kapatid Foundation, Inc. in persuading people to donate after Tropical Storm Maring - Negranza, Jessica N.
This study examined the efficiency of social networking sites (SNSs) in increasing the likelihood of people to donate for the victims of calamities. In this study, the researchers chose to examine the efficiency of Facebook and Twitter as used by the TV networks' foundations during Tropical Storm Maring in 2013. The foundation analyzed are GMA Kapuso Foundation, Inc., ABS-CBN Foundation, Inc., and TV5 Alagang Kapatid Foundation, Inc. -- Author's abstract.